Malefactive uses of giving/receiving expressions: The case of te-kureru in Japanese. (8th March 2018) - Obana, Yasuko; Haugh, Michael
Abstract : The Japanese auxiliary te-kureru ('giving to the speaker or the speaker's group member') is traditionally assumed to connote gratitude, favour or 'politeness', and thus is regarded as a benefactive. In this paper we argue that te-kureru does not inherently indicate benefaction, but rather that its occurrence, whether it is grammatically obligatory or optional, serves to intensify the speaker's affective stance towards the referent in that given context. This accounts for the way in which this auxiliary may also contribute to expressions of sarcasm, anger, contempt or retaliation. We propose that because malefaction is unfavourable to the speaker, the speaker deliberately takes a lower stance through te-kureru, making as if the other's unfavourable action was taken from a higher position, which amounts to a putting down or deliberate neglect of the speaker. We also suggest that the auxiliary remains affectively neutral if the context is neither benefactive nor malefactive in orientation.